Treatment of displaced, proximal, humeral, epiphyseal fractures with a two-prong splint - Karatosun, V; Ünver, B; Alici, E; Serin, E (Lippincott Williams & Wilkins, 2003)
To evaluate the use of a two-prong splint for displaced, proximal, humerus, epiphyseal fractures, seven children with Neer-Horwitz Classification Type 3-4 fractures of the proximal humerus were retrospectively investigated. After closed reduction, fracture stabilization was accomplished with the use of a two-prong splint, and at an average follow-up of 54 months (range 48-62 months), all children were evaluated radiographically and functionally. There were no complications, and all patients had full painless range of shoulder and elbow motion, without malunion, joint incongruity, nonunion, avascular necrosis, and limb-length discrepancy. The results did not change over time. Treatment of displaced, proximal, humeral, epiphyseal fractures with a two-prong splint gives satisfactory results while allowing immediate motion and gradual reduction of the fragments without anesthesia, and it may be the treatment of choice for such injuries in children.
Keywords: proximal humerus; epiphyseal fracture; displaced fracture; children; two-prong splint; nonoperative treatment